Unveiling Research Trends in Philippine Mathematics Education: A Comprehensive Bibliometric and Systematic Analysis - Acopio, Ma. Kathleen Mae Geremias (FKIP Universitas Lampung, 2025)
Unveiling Research Trends in Philippine Mathematics Education: A Comprehensive Bibliometric and Systematic Analysis. Objectives: This study aimed to conduct a bibliometric analysis of mathematics education research affiliated with the Philippines, as indexed in the Scopus database, covering the period from 2006 to 2024. The objective was to map publication trends, identify prolific authors and institutions, and analyze thematic and disciplinary classifications to assess the country’s research visibility and productivity. Methods: Data were retrieved from the Scopus database due to its comprehensive coverage of peer-reviewed academic publications. The search query used was: AFFILCOUNTRY (